PERAN EKONOMI SYARIAH DALAM MENDORONG PERTUMBUHAN EKONOMI HIJAU DAN BERKELANJUTAN - Gunawan, Erpan; Jusniar, J; Mariani, Kellin Rossa (Pusat Riset dan Publikasi, 2024)
Green economy and sustainable development has become a major concern in global development discourse to address environmental degradation and climate change. Sharia economy with its inherent Islamic principles and values ??has great potential to contribute to driving environmentally friendly economic growth and sustainable. This article aims to explore the role of Islamic economics in promoting green economy and sustainable development through a qualitative approach with literature study and descriptive analysis. Based on the results of a review of various relevant literature, it can be concluded that Islamic economics has a concept that is in line with the green economy and sustainable development. The principles of Islamic economics, such as justice, balance, and blessings, help create sustainable economic growth, a sustainable environment, and sustainable social welfare. The Islamic economic system also has synergy with the concept of a green economy in sustainable development that includes social principles and business ethics. Although there are still challenges in its implementation, Islamic economics offers a holistic and sustainable view in the management of economic resources so that it can create a new economic paradigm that promises to achieve balanced economic development between economic, social and environmental aspects.